Squarrosine A and Pyrrolhuperzine A, New Lycopodium Alkaloids from Thai and Philippine Huperzia squarrosa - Nilsu, Thanasan; Thorroad, Sakornrat; Ruchirawat, Somsak; Thasana, Nopporn (Planta Medica, 2016)
Two new Lycopodium alkaloids, squarrosine A (1) and pyrrolhuperzine A (2), were isolated from the Thai and Philippine plant Huperzia squarrosa. (R)-2-Piperidineacetic acid (5) was a known alkaloid, but has now been isolated for the first time from a natural source. Their structures were elucidated using extensive spectroscopic analyses and, for pyrrolhuperzine A (2), confirmation by chemical transformation. The new compounds exhibited moderate acetylcholinesterase inhibitory activities.
Keywords: Huperzia squarrosa; Lycopodiaceae; Lycopodium alkaloid; Huperzine A derivative; Acetylcholinesterase inhibitor